Porte ilegal de arma de fogo desmuniciada: crime ou indiferente penal? - França, Andressa Martins (2008)
The conduct of carrying a firearm without ammunition, according to the positioning of some douctriners, followed by understanding of the Supreme Federal Court, is indeed unusual, for it lacks the capability needed to affecting the characterization of crime. However, there are douctriners that understand that the conduct is typical, following the positioning of the Superior Court of Justice, because, despite the gun devoid of ammunition is not able to make shots, serves as an instrument for the practice of various crimes, bringing in risk legal property of great importance, such as security and public order. The understanding of the Supreme Federal Court, to consider that this conduct is not a crime, is based on various principles of criminal law, such as insignificance, proportionality, minimum intervention, among others, as well as theories that seek to define the concept of crime, as the theory of typical conglobant characteristics. This position, as will be demonstrated, although possessing extensive ballast in doctrine, is against the legislation applicable to the case in kind, which is the Statute of Disarmament, since it was edited with the goal of providing the criminal law and a society instrument of greater repression against crime, aiming to curb the rising crime and public insecurity.